Application of 5G mobile nurse workstation combined with intelligent nursing interaction system in management of nursing shift (5G移动护士站系统结合护理白板在护理交接班中的应用) - HUANG Liming (黄丽明); LI Chunrong (李春容) (中西医结合护理)
Objective To investigate the effect of 5G mobile nurse workstation combined with intelligent nursing interaction system on improving quality of nursing shift. Methods A nursing shift procedure was established, and 5G mobile nurse workstation combined with HIS-based intelligent nursing interaction system was adopted in daily management of nursing shift. The nurse awareness of illness condition, omission of nursing shift information and duration of nursing shift were measured. Results The rate of awareness of illness condition was increased after adopting 5G mobile nurse workstation combined with intelligent nursing interaction system(P＜0. 01). There was a drop in omission rate of nursing shift information and duration of nursing shift(P＜0. 01). Conclusion Adopting 5G mobile nurse workstation combined with intelligent nursing interaction system may help to increase nurse awareness of illness condition, reduce the omission of nursing shift information and improve the quality of nursing. (目的 探讨应用5G移动护士站系统结合护理白板提高交接班质量的效果。方法 制定交接班流程, 利用5G移动护士站系统, 基于医院信息系统的护理白板显示功能, 共同用于护理交接班。比较实施前后护士对患者病情知晓率、交接班遗漏率和交接班时间。结果 实施后护士对患者病情知晓率高于实施前(P＜0. 01), 交接班遗漏率比实施前降低(P＜0. 01), 交接班时间比实施前减少(P＜0. 01)。结论 利用5G移动护士站系统结合护理白板改进交接班流程, 提高了护士对患者病情知晓率, 降低了交接班遗漏率, 提高了护理工作质量。)